2017
DOI: 10.18203/2394-6040.ijcmph20174184
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension: prevalence, awareness, treatment and control in a rural area of North Kerala, India

Abstract: Background: High blood pressure is prevalent all over the world and is one of the major causes of cardiovascular morbidity and mortality. In considerable proportion of cases the disease tends to be asymptomatic for prolonged time, hence also labelled as “silent killer”. Awareness, treatment, and control of hypertension remain major challenges worldwide. The objective of this study was to determine the prevalence, awareness, treatment and control of hypertension in Northern Kerala. Methods: A community-based cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
2
1
Order By: Relevance
“…Compared with previous systematic reviews on the region-specific prevalence of hypertension which found about 25% of rural population and 21% of the South India population had hypertension ( 33 ), about 27% of participants in our study (mostly rural residents) were found to have hypertension. The level of hypertension awareness, treatment, and control in previous studies conducted in Kerala varies across districts and age groups, with lower awareness found in Trivandrum (16.8%) ( 34 ), Kannur district (38.7%) ( 14 ), and higher in Ernakulam district with older age groups (78%) ( 15 ), comparing to 54% found in our study in rural Kerala. Compared with one of the earliest cohorts in Kerala to study the incidence of hypertension ( 35 ), we found slightly higher rates of awareness (54.4 vs. 42.9%) and treatment (25.5 vs. 22.9%).…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Compared with previous systematic reviews on the region-specific prevalence of hypertension which found about 25% of rural population and 21% of the South India population had hypertension ( 33 ), about 27% of participants in our study (mostly rural residents) were found to have hypertension. The level of hypertension awareness, treatment, and control in previous studies conducted in Kerala varies across districts and age groups, with lower awareness found in Trivandrum (16.8%) ( 34 ), Kannur district (38.7%) ( 14 ), and higher in Ernakulam district with older age groups (78%) ( 15 ), comparing to 54% found in our study in rural Kerala. Compared with one of the earliest cohorts in Kerala to study the incidence of hypertension ( 35 ), we found slightly higher rates of awareness (54.4 vs. 42.9%) and treatment (25.5 vs. 22.9%).…”
Section: Discussioncontrasting
confidence: 73%
“…In India, several studies have investigated the prevalence of hypertension awareness, treatment, and control ( 14 16 ). Factors associated with these rates were only explored in cross-sectional studies and also, only a limited number of potential factors were investigated ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension is one of the leading causes of disease in India and causes huge health and economic burdens 1‐3 . While blood pressure (BP) control has improved substantially in many high‐income countries, effective management of hypertension in low‐ and middle‐income settings remains challenging 4,5 . Joint interventions that utilize drug‐based strategies, dietary interventions, and other behavioral approaches are advocated by most national and international hypertension societies, including in India 6 .…”
Section: Introductionmentioning
confidence: 99%